Fruit yield of strawberry plants inoculated with Azospirillum brasilense RLC1 and REC3 under field conditions. - Salazar, Sergio Miguel (2012)
The beneficial effect of inoculating with Azospirillum brasilense on crop productivity has been widely described in different crops, but its extensive use in strawberry typical agricultural field environments is scarcely documented. The objective of this study was to quantify the fruit yield of strawberry plants (Fragaria ananassa Duch.) inoculated with A. brasilense (strains RLC1 and REC3) under typical dryland farming conditions. The study was performed during 2006-2009 growing seasons, evaluating root inoculated and non-inoculated strawberry plants cultivar ‘Camarosa’ in Tucumán, Argentina. The inoculated plants exhibited more vigorous vegetative growth and increased the total fruit yield by 8.5% and marketable yield by 7%, as compared with non-inoculated plants.